Pencegahan Stunting Melalui Pilar 1 Stop Buang Air Besar Sembarangan Di Kelurahan Waehaong Kecamatan Nusaniwe Kota Ambon - Rahma Tunny; Ernawati Hatuwe; Mirdat Hitiyaut; Asih Dwi Astuti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
Stunting is a condition where a person's height is shorter than the height of other people in general (of the same age). Stunted (short stature) or low height/length for age is used as an indicator of chronic malnutrition which describes the history of under-nutrition in toddlers over a long period of time. The design used in this research is a research design with a correlational/causal analytical method with a cross sectional design. The population in this study was 82 mothers of toddlers. The sampling technique used in this research was the Slovin formula. The total sample in this study was 82 mothers of toddlers. The results of the research show that there is a significant relationship between healthy latrines and the incidence of stunting among toddlers in Waehaong subdistrict, Nusaniwe subdistrict, Ambon City with a p value of 0.000. For the government, in this case, village officials, especially village heads, are expected to be able to facilitate and plan budget procurement for environmental sanitation improvements such as improving healthy latrine facilities and making efforts to improve residential environmental sanitation programs with healthy behavior. Health workers, especially sanitarian officers, can carry out their role as educators by providing education related to the health of the family environment in order to increase knowledge about maintaining and creating a healthy family environment. And can also provide education about healthy latrine facilities and strive to improve residential environmental sanitation programs with healthy behavior.